A historical retrospective and research subjects of the empirical research in performance planning (Per Musi, 2015)
This article gives an overview of the main subjects investigated by the scientific research from an historical retrospective of empirical research in Performance Planning. Knowing that the research object has many ramifications and specificities, it is possible to insert a great part of the subjects of research within a broad thematic category. In this context, this article defines the categories in which each theme related to performance planning can be inserted within Musical Performance.